The role of ubiquitin proteasomal system and autophagy-lysosome pathway in Alzheimer’s disease - Zhang, Yuan; Chen, Xu; Zhao, Yanfang; Ponnusamy, Murugavel; Liu, Ying (Reviews in the neurosciences, 2017)
Alzheimer’s disease (AD) is the most common neurodegenerative disorder leading to dementia in the elderly population. AD is associated with the buildup of β-amyloid and tau, which aggregate into extracellular plaques and neurofibrillary tangles. Although the exact mechanism of pathological process of AD is unclear, the dysfunction of protein degradation mechanisms has been proposed to play an important role in AD. The cellular degradation of abnormal or misfolded proteins consists of three different mechanisms: the ubiquitin proteasomal system (UPS), autophagy-lysosomal pathway (ALP), and interaction of molecular chaperones with UPS or ALP. Any disturbance to these systems causes proteins to accumulate, resulting in pathological process of AD. In this review, we summarize the knowledge of protein degradation pathways in the pathogenesis of AD in light of the current literature. In the future, the regulation UPS or ALP machineries could be the cornerstones of the treatment of AD.